2020
DOI: 10.1002/jaoc.12083
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship of Emotional Intelligence and Cultural Empathy in Addiction Counselors

Abstract: The purpose of this study was to examine the relationship between emotional intelligence and cultural empathy in addiction counselors. A hierarchical regression analysis revealed emotional intelligence accounted for most of the variance in cultural empathy in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Furthermore, technological addictions are of recent interest (Gugliandolo et al, 2019), and EI has been found to be a protective factor against problematic internet behaviour (Arrivillaga et al, 2020;Hsieh et al, 2018;Sechi et al, 2020;Wang & Zhang, 2020), and smartphone use (Arrivillaga et al, 2020;Busch & McCarthy, 2021;Mascia et al, 2020). Finally, EI and EC may not only act as protective factors against addiction behaviours, but may also represent an important adjuvant for counsellors providing support for people with addiction, given addiction counsellors with higher EI have been found to display higher cultural empathy (Smith et al, 2020). Taken together, these findings showcase the societal relevance of EI and EC to better understand addiction.…”
mentioning
confidence: 99%
“…Furthermore, technological addictions are of recent interest (Gugliandolo et al, 2019), and EI has been found to be a protective factor against problematic internet behaviour (Arrivillaga et al, 2020;Hsieh et al, 2018;Sechi et al, 2020;Wang & Zhang, 2020), and smartphone use (Arrivillaga et al, 2020;Busch & McCarthy, 2021;Mascia et al, 2020). Finally, EI and EC may not only act as protective factors against addiction behaviours, but may also represent an important adjuvant for counsellors providing support for people with addiction, given addiction counsellors with higher EI have been found to display higher cultural empathy (Smith et al, 2020). Taken together, these findings showcase the societal relevance of EI and EC to better understand addiction.…”
mentioning
confidence: 99%